In our own time - WNET (Television station : New York, N. Y.). (West Long Branch, N. J. KULTUR, 1989)
Examines why the appearance of abstract expression caused the United Statesto become a center for the visual arts. Reviews the diversity of styles in the postwar period, including the work of Pollock, Wharhol, Oldenburg.
Also examines the explosive internationalization of the qrt world in the 1970s and 1980s.
An Annenberg/CPBB project.
VHS.
Keywords: Abstract expressionism -- United States; Art, America; Art, Modern -- 20th century -- United States; Art -- International Cooperation; Abstract impressionism; Art -- Modern -- 20th century